Design, synthesis, and assessment of a de novo affinity adsorbent for the purification of recombinant human erythropoietin. Issue 11 (16th May 2013) - El Khoury, Graziella; Wang, Yian; Wang, Di; Jacob, Shaleem I.; Lowe, Christopher R.
ABSTRACT This work describes the assessment of a de novo synthetic affinity ligand for recombinant human erythropoietin (rHuEPO), based on the multicomponent Ugi reaction. Four Ugi ligands were designed based on the X‐ray crystallographic structure of the complex between human erythropoietin and site 1 of its cell‐surface receptor (EPObp)2; screening of the ligands with pure rHuEPO samples identified a lead ligand (A9C10I8) immobilized on aldehyde‐functionalized agarose beads, which was able to bind and elute erythropoietin, as determined by SDS–PAGE and Western blot analyses. Furthermore, small‐scale affinity chromatography performed on the immobilized adsorbent showed its ability to isolate rHuEPO from a spiked mammalian cell supernatant with a purity of ∼80%, as estimated with gel densitometry. This approach could lead to the development of a cost‐effective downstream process for rHuEPO, as an alternative to the current multi‐step purification protocols. Biotechnol. Bioeng. 2013;110: 3063–3069. © 2013 Wiley Periodicals, Inc.